Multimedia BASICS - Suzanne Weixel (Thomson/Course Technology, 2004)
This new text from our BASICS series provides comprehensive coverage of many multimedia topics including graphics, animation, video, presentations, desktop publishing, and web pages. An excellent foundation for any mulitmedia or website design curriculum